Integrating Thomas Lickona’s Character Education Theory through the BTQ Program: Strengthening Religious Character in Islamic Elementary Schools - Fitri Alifah; Aufia Aisa; Dian Kusuma Wardani (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2026)
This study aims to describe the implementation of the Qur’anic Reading and Writing Program (Baca Tulis Al-Qur’an/BTQ) in shaping students’ religious character at MI Al-Azhar Sambongdukuh Jombang. The study employed a qualitative approach with data collected through observation, interviews, and documentation. The findings revealed that the BTQ program was implemented through habituation in reading and memorizing the Qur’an, teachers’ role modeling, and continuous guidance integrated into daily school activities. Through these activities, students showed improvement in their ability to read and write the Qur’an, while also developing disciplined, responsible, patient, and respectful attitudes toward teachers and their surrounding environment. The findings further indicate that the BTQ program is closely aligned with Thomas Lickona’s character education theory, which emphasizes the integration of moral knowing, moral feeling, and moral action in character formation. Students not only understood religious values cognitively, but also began to develop a love for reading the Qur’an and applying its values in their daily lives. However, the implementation of the program still faced several challenges, including differences in students’ abilities, limited instructional time, and insufficient parental assistance at home. Therefore, stronger collaboration between the madrasah and parents is needed to ensure that the development of students’ religious character can be carried out optimally and sustainably.